If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + 7 + 4(3m + -5) = 5(m + 5) Reorder the terms: 5m + 7 + 4(-5 + 3m) = 5(m + 5) 5m + 7 + (-5 * 4 + 3m * 4) = 5(m + 5) 5m + 7 + (-20 + 12m) = 5(m + 5) Reorder the terms: 7 + -20 + 5m + 12m = 5(m + 5) Combine like terms: 7 + -20 = -13 -13 + 5m + 12m = 5(m + 5) Combine like terms: 5m + 12m = 17m -13 + 17m = 5(m + 5) Reorder the terms: -13 + 17m = 5(5 + m) -13 + 17m = (5 * 5 + m * 5) -13 + 17m = (25 + 5m) Solving -13 + 17m = 25 + 5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5m' to each side of the equation. -13 + 17m + -5m = 25 + 5m + -5m Combine like terms: 17m + -5m = 12m -13 + 12m = 25 + 5m + -5m Combine like terms: 5m + -5m = 0 -13 + 12m = 25 + 0 -13 + 12m = 25 Add '13' to each side of the equation. -13 + 13 + 12m = 25 + 13 Combine like terms: -13 + 13 = 0 0 + 12m = 25 + 13 12m = 25 + 13 Combine like terms: 25 + 13 = 38 12m = 38 Divide each side by '12'. m = 3.166666667 Simplifying m = 3.166666667
| -2-9=5x+6-4x | | 4x+6-3=12 | | x+17=38 | | -2x-2x=19-7 | | 11+3(3y+5)= | | n/2=-4 | | -10y=-90 | | 2x-21=-.8 | | 2x-21=-8 | | 11n=10n+23 | | 6(x+7+8y)= | | (y-9)-(y+4)=6y | | 2x-21=.8 | | 2x-21=.08 | | 10x+2=8x+22 | | 2x/(x+4)=5 | | 2r^3+16r^2=40r | | 0.5(2(-15)-4)=-17 | | P=80-2P | | 6x-15-x=6x-13 | | (4-x)+2=9 | | 6p-(5p+5)=8-2(p+12) | | 7(3+c)=6(c-5) | | z^2-3z-108=0 | | 0.4(2(58)+4)=48 | | z^2-6z-12=0 | | 12(8c-1)-4=94c+12 | | 3s-8=s-2 | | 14+3(x+10)=7(2x+4)+x | | 0.27-0.03(x+3)=-0.02(1-x) | | 0.4(2x+4)=48 | | 2z^2-18z=-72 |